2023
DOI: 10.1039/d2sc04911b
|View full text |Cite
|
Sign up to set email alerts
|

Dual ligand approach increases functional group tolerance in the Pd-catalysed C–H arylation of N-heterocyclic pharmaceuticals

Abstract: Ligand combination of a 2-pyridone with traditional phosphines enables superior functional group tolerance in the C–H (hetero)arylation of pharmaceutically relevant N-heterocyclic scaffolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In contrast to the above examples, the Pd‐catalyzed C‐phenylation of imidazo[1,2‐ a ]pyridine with bromobenzene arose with less than 5% yield in the presence of catalytic amounts of AcOH, PhCO 2 H or t ‐BuCO 2 H [38] …”
Section: Formation Of C(sp2)−c(sp2) Bondsmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast to the above examples, the Pd‐catalyzed C‐phenylation of imidazo[1,2‐ a ]pyridine with bromobenzene arose with less than 5% yield in the presence of catalytic amounts of AcOH, PhCO 2 H or t ‐BuCO 2 H [38] …”
Section: Formation Of C(sp2)−c(sp2) Bondsmentioning
confidence: 83%
“…In contrast to the above examples, the Pdcatalyzed C-phenylation of imidazo[1,2-a]pyridine with bromobenzene arose with less than 5% yield in the presence of catalytic amounts of AcOH, PhCO 2 H or t-BuCO 2 H. [38] Both regioselectivity and yield of the Heck reaction of bromobenzene with 1,3-dimethyluracil in DMF were improved by addition of t-BuCO 2 H (Scheme 4a). [39] While the reaction arises via PhPdBr under acid-free conditions, the cationic palladium intermediate PhPd � t-BuCO 2 � would be involved in the presence of t-BuCO 2 H, its formation being favored by the polarity of the solvent.…”
Section: Intermolecular Reactionsmentioning
confidence: 91%
“…26 Traditional methods for synthesizing substituted imidazo-[1,2-a]pyridines involve palladium-catalyzed couplings, requiring prefunctionalization of the ring as an iodide or bromide, which can be cumbersome. 27 The one-pot, two-stage reaction method introduced in this work is straightforward, efficient, and particularly suitable for synthesizing imidazo[1,2-a]pyridines with long alkyl chains (Scheme 6). Imidazo[1,2a]pyridine 53 was obtained with an 89% yield through the reaction of 1-phenylethanol and 2-aminopyridine.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…1 H NMR (500 MHz, CDCl 3 ) δ 7.40 (br t, J = 7.7 Hz, 1H), 7.37−7.31 (m, 3H), 7.29−7.26 (m, 3H), 7.18−7.14 (m, 1H), 3.34 (hept, J = 6.8 Hz, 2H), 1.22 (d, J = 6.9 Hz, 12H). 13 (27). It was obtained as a white crystal (106.4 mg, 40%), mp 147.8−149.6 °C.…”
Section: (S)-5-decyl-n-(1-phenylethyl)thiazol-2-amine (20) It Was Obt...mentioning
confidence: 99%
“…More recently, it has been shown that XAS techniques are very productive for addressing various mechanistic issues also in homogeneous catalysis (e.g., refs ). The success of applying XAS to homogeneous catalysts based on 4d metals inspired us to try this technique for in situ monitoring of our reactions as well.…”
Section: Introductionmentioning
confidence: 99%